THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL ATTITUDE, AND DEMOGRAPHIC FACTORS ON INVESTMENT DECISIONS (CASE STUDY: FEMALE EMPLOYEES OF IIK STRADA INDONESIA KEDIRI) - Susanti, Titin; Arisyahidin, Arisyahidin; Mutiara, Nisa (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
Mastering fundamental financial proficiency and expertise in finance in managing financial resources can enhance each individual's welfare so that they can grasp national concerns in the financial sector. This is because such knowledge and skills are necessary to manage financial resources. A person's capacity to use the financial institution system might be hindered by their lack of financial literacy, which can also harm prosperity. This study aimed to investigate the considerable influence that financial literacy and financial attitudes are of paramount importance in personal finance., and demographic characteristics have on how individuals make decisions regarding financial investments. In this study, a descriptive technique was taken in conjunction with a quantitative one. A total of 67 participants were sampled from the population for this study. In order to collect data for this study, the researchers utilized a questionnaire. The research utilized a method known as multiple regression analysis for the test. The study's findings explain concurrently why financial literacy, financial attitudes, and demographic characteristics play a substantial role in investment decision-making. It is thought to be influential because the level of financial literacy, financial Attitude, and demographic characteristics all contribute to the behaviour of investment decision-making, and the better they are, the more influential it is thought to be. According to the findings of this research, employers and investors should be able to meet their expectations about their knowledge of how to comprehend financial literacy properly.Â Keywords: demography, investment, finance, decision, literacy, Attitude